The self, the other and the identity(ies): identity representations before the character Chico Bento and implications for Rural Education - Mônica Andrade Modesto; Felipe Alex Santiago Cruz (Universidade Federal do Norte do Tocantins, 2022)
The present study reflects about the concept of identity and the identity perception of subjects in the field, based on a study carried out after carrying out a pedagogical activity with students from a school located in the field. To this end, the writing is anchored in a theoretical contribution referring to the field of Sociology to deal with identity (Stuart Hall, 2005, 2006); Zygmunt Bauman (1999, 2003, 2005) and Roger Chartier (1991) and Education to encompass Rural Education (Miguel Arroyo, 1999, 2011); Roseli Caldart (2011) and Ângela Pires (2012)). Under the aegis of the discourse analysis based on Eni Orlandi (2013), the data revealed that the participating subjects find it difficult to perceive themselves similar to the characteristics presented by the character of the field - Chico Bento - in the cartoons and feel comfortable approaching them the image of the city subject - Zeca, cousin of Chico Bento who lives in the urban area. The speeches also demonstrated the existence of the Translation phenomenon present in the speeches and representations of the subjects, which is legitimized by the invisible curriculum of the modi vivendi and operandi of the living in the countryside who, through the elements present in daily life and in school culture, have the feeling of belonging undermined as the valorization of the modi vivendi and operandi of the urban space surpasses the rural space.